Behavior of Full-Scale Porous GFRP Barrier under Blast Loads. (4th October 2015) - Asprone, D.; Prota, A.; Manfredi, G.; Nanni, A.
Abstract : This research paper is part of the SAS (Security of Airport Structures) Project funded by the European Programme for Critical Infrastructure Protection, whose objective was to develop and deploy a fiber reinforced polymer (FRP) fencing system intended to protect airport infrastructures against terrorist acts. In the paper, the efficacy of the proposed glass FRP discontinuous (porous) barrier under blast loads is presented by showing the results of the blast test campaign conducted on full-size specimens with a focus on the reduction of the blast shock wave induced by the barrier. A simplified model predicting the reduction of the shock wave beyond the barrier is proposed and validated via the experimental data obtained in the project.